Function and clinical relevance of the ligamentum teres: a current concept. Issue 4 (July 2015) - Martin, RobRoy L.; Martin, Hal David
Abstract : Despite a growing interest in the ligamentum teres, its role in hip stability has not been investigated until recently. The purpose of this paper was to review current literature and define the function and clinical relevance of the ligamentum teres. Based on recent studies the function of the ligamentum teres can be defined as a rotational stabilizer in all hip positions and the primary rotational stabilizer in the upper range of flexion, greater than 90°. The function of the ligamentum teres may be described using a ball and string model where rotational movements of the femoral head that occur in the transverse and frontal planes cause the ligamentum teres to act as a sling as it wraps around the femoral head. Also as the ligamentum teres tightens, it pulls the femoral head into the actetabulum to increase stability at the end range of hip motion. This stabilizing function becomes important when the capsular ligaments are in a loose pack position of hip flexion, in those with osseous risk factors for instability and also may be more important in those with capsular laxity. The ligamentum teres test can be used to detect pain associated with partial tears of the ligamentum teres while a squat test may be useful to identify those with hip instability associated with complete ligamentum teres tears and osseous risk factors for instability. The results of these studies also support theories that the ligamentum teres could be injured in a highly active population with nontraumatic injuries and/or abnormal acetabular geometry.